Utilization of indigenous food plants in Uganda : A case study of south-western Uganda - Musinguzi, Enock; . Kikafunda, Joyce K.; Kiremire, B. T. (African Journal of Food, Agriculture, Nutrition and Development, 2006)
The purpose of the study was to document and establish the traditional processin methods of indigenous food plants in Rukungiri district. In order to establish the status and level of utilization and processing of indigenous food plants in southwestern Uganda, a baseline survey was carried out using a participatory method of data collection. Respondents in Rukungiri district cited a total of 94 plants that were used for food. Some of the food plants were classified as indigenous to the area, while others were classified as exotic. The food types generally fell into five broad categories, namely; vegetables, fruits, roots/tubers, pulses and cereals. Vegetables and fruits were the most commonly used food plants and the Amaranths species were found to be the most popular vegetables, whereas wild plums (Carissa edulis) and gooseberries (Physalis minima) were cited among the